Prevalence and ethnic distribution of helicobacter pylori infection among endoscoped patients in north eastern peninsular Malaysia - Kaur, Gurjeet; Naing, Nyi Nyi (2002)
There exists significant difference in prevalence of H. pylori infection among different societies and ethnic groups, even within the same country. Malaysia with its multiracial population provided a valuable opportunity to study the racial distribution of this infection.The aim of this study was to determine the prevalence and ethnic distribution of Helicobacter pylori infection in an endoscoped population in the North Eastern Peninsular Malaysia.Pathology records of 400 consecutive gastric biopsies received at the pathology laboratory in a university hospital were reviewed. Demographic data of patients including their ethnic groups were documented. H. pylori infection was ascertained by histological evaluation of the gastric biopsies. Univariate and multivariate analysis were applied to determine the prevalence of H.pylori infection in the sampled population and the difference in prevalence among the ethnic groups. The overall H. pylon infection prevalence rate was unusually low at 13 .5%) (54 of 400) in this region. The prevalence among the races were as follows: Malay 6.6% (17/256). Chinese 24.1% (27/112) and Indian 2R.6(% (6/21). Gender and age were not significant risk factors for 1-1. pylon infection. However there was an increased risk of H. pylon infection in Chinese (OR= 4.46, 2.3-8.6) and Indians (0R=5.6,1.9-16.3) compared to Malays.The difference in prevalence of H. pylori infection between the three major ethnic groups concurs with other studies done in Malaysia. The reason for this interesting finding is uncertain and is suspected to be due to different environmental, genetic and socio-cultural practices in the various races.